Faktor-Faktor yang Berhubungan dengan Perilaku Pemeriksaan Payudara Sendiri (SADARI) pada Siswi Kelas XII di SMK Negeri 3 Cilegon Banten - Lindawati, Refi; Yunarsih, Nani (ProHealth Journal, 2021)
Background : Breast cancer is a malignant tumor formed from breast cells that grow and develop uncontrollably. One of the efforts to detect early is by breast self-examination (SADARI). The purpose of this study was to determine the factors related to breast self-examination behavior (SADARI) in class XII students at SMK Negeri 3 Cilegon Banten in 2021. Method : The type of research is quantitative using a cross-sectional approach. The total population was 252 female student and a sample of 81 technical student used the Random Sampling technique. The analysis used univariate and bivariate analysis with the Square chi test. Result : The results showed that 71.8% of female students did not do SADARI, 60.3% of femalestudents had less knowledge with p-value = 0.0 14, 78.2% of students had a positive attitude towards SADARI with p-value = 0.857, 74.4% of students did not get family support with p-value = 0.005, 60.3% of female students are less likely toget the role of health workers with a p-value = 0.014. Conlusion : The conclusion that knowledge, family support and the role of health ten aga have a relationship to SADARI behavior while attitudes have no relationship to SADARI behavior.